PENYULUHAN KESEHATAN KEPADA MASYARAKAT DI DESA KRESNOMULYO DUSUN 007 TENTANG PENYAKIT ASAM LAMBUNG TAHUN 2024 - Putri, Diah (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2024)
Many people in Kresnomulyo still have irregular eating patterns and unhealthy lifestyles which can cause various kinds of stomach diseases. This activity aims to solve the problems that occur in the Kresnomulyo Village community with an outreach method that uses assistance in the form of leaflets and provides alternative treatments using herbal plants. This disease can be prevented by maintaining a good diet and lifestyle. Based on the outreach results, the results showed that there were some people affected by stomach acid disease and this outreach activity was attended by 26 people. In this activity, the community responded positively to the activities that had been carried out so that they ran well and smoothly.